On the margins of belonging confronting cosmopolitanism in the late modern age - Lee, R.L.M. (SAGE Publications (UK and US), 2010)
Recent debates on cosmopolitanism have focused on the problem of solidarity and belonging within the context of the nation-state. In particular, the idea of belonging is taken to be a key feature of social organization related to the institutions of the nation-state. Yet the complexities of belonging have not been closely examined. In this regard, the idea of liquid modernity and the recent work on racialized labour pose new questions concerning the limits of belonging. Weakening social bonds due to liquidity and new forms of belonging arising from resistance to racialization suggest paradoxical conditions problematizing the meaning of cosmopolitanism. The aim of this article is to articulate the significance of liquidity and marginality in conceptualizing the relation between the nation-state and cosmopolitanism.